A Fully Differential Variable Gain Amplifier for Portable Impedance Sensing Applications - Pérez Bailón, Jorge; Ramírez-Angulo, Jaime; Calvo, Belén; Medrano, Nicolás (Jornada de Jóvenes Investigadores del I3A, 2019)
This paper presents a Variable Gain Amplifier (VGA) designed in a 0.18 μm CMOS process to operate in an impedance sensing interface. Based on a transconductance-transimpedance (TC-TI) approach with intermediate analog-controlled current steering, it exhibits a gain ranging from 5 dB to 38 dB with a constant bandwidth around 318 kHz, a power consumption of 15.5 μW at a 1.8 V supply and an active area of 0.021 mm2.